Pengendalian Hipertensi dengan Menerapkan Perilaku “PATUH” - shofia siti adawiah; Rosmalina Hoerunisa; Salwa Amalia; Sari Puspayanti; Sinta Siti Rahmah (Yayasan Inspirasi El Burhani, 2021)
Introduction: Hypertension is a major problem in Indonesia, with a prevalence of 25.8%. Cases are increasing due to several reasons including lack of knowledge, people's behavior shows bad behavior to prevent high blood pressure. One of the factors that cause hypertension is due to genetics, lifestyle and behavior. Low awareness of high blood pressure treatment is a major cause of complications. Objective: This counseling aims to increase general knowledge about preventing complications of hypertension. This is done through visits and training with community discussions and blood pressure checks. Method: The method carried out is in the form of visits and providing counseling accompanied by observations of the community, then blood pressure checks are carried out. The counseling will be held on November 7, 2021 in Wanareja District. Plus providing education about hypertension, then leaflets to provide insight to the public equipped with free blood pressure activities. Result: The evaluation results show that it has been carried out well in accordance with the indicators results and criteria on the Evaluation Sheet instrument. The Evaluation Sheet is based on five dimensions,namely Punctuality and Duration, Participation, Knowledge, Job Description and Solving The evaluation sheet is filled out by two independent observers Conclustion: In accordance with the results of the evaluation, outreach activities for controlling hypertension by implement PATUH behavior (regular health checks and must follow the recommendations)from the doctor, Overcome the disease with good, correct and regular treatment, but diet together good nutrition, Strive for safe physical activity, Avoid people who like smoking, substancescarcinogenic and alcohol). has been accompanied by a fairly precise time indicator as well as Duration, Participation, Knowledge, Job Description and Problem Solving.